A comparison of the acute toxicities using moderate hypo-fractionated intensity-modulated radiation therapy or volumetric modulated arc therapy for the treatment of early-stage prostate cancer. Issue 3 (11th June 2015) - Elith, Craig A.; Dempsey, Shane E.; Warren-Forward, Helen M.
Abstract Aim This study compared the acute toxicities reported during radiotherapy treatment using either intensity-modulated radiation therapy (IMRT) or volumetric-modulated arc therapy (VMAT) to deliver a moderate hypo-fractionated treatment for early-stage prostate cancer. Material and methods Acute toxicities are routinely reported at the clinical site for all patients using the Common Terminology Criteria for Adverse Events. Toxicity assessment is performed on day 1 of treatment, then once weekly thereafter. The recorded toxicities of 40 cases treated with five-field IMRT, and 32 cases treated using VMAT were retrospectively compared. All cases were prescribed 73·68 Gy in 28 fractions. Eight symptoms were assessed; diarrhoea, proctitis, fatigue, pain, dermatitis, urinary frequency, urinary retention and urinary tract pain. Results In terms of the overall toxicity recorded, VMAT was shown to reduce the toxicities of dermatitis, fatigue, pain and urinary frequency (p<0·05). Using IMRT, grade 2 toxicities were reported for proctitis, pain, urinary frequency, urinary retention and urinary tract pain. Using VMAT, grade 2 toxicities were reported for urinary frequency and urinary retention. Findings The research reported here is one of the first publications to demonstrate that VMAT is associated with decreased toxicities compared with IMRT for the treatment of early-stage prostate cancer.